Ultrasound in Detection of Developmental Hip Dysplasia in Premature Born Children - Misanovic, Verica (Acta Inform Med, 2015)
INTRODUCTION: Developmental hip dysplasia represents the most common deformation of locomotor system in children. Developmental modulation of the hip is expressed during first year of life which is important for early diagnosis and treatment. Therefore, in the practice, it is very important to set a diagnosis early with application of simple and convenient methods (ultrasound) in order to achieve fast and efficient therapeutical effect and avoid permanent disability. AIM: The aim of this paper is to point out the increase of prematurely born infants and their survival thanks to the development of Unit for Intensive Neonatal Care at the Pediatric Clinics in Sarajevo. MATERIAL AND METHODS: Clinical investigation included 150 infants (77 girls and 73 boys) in whom the developmental hip dysplasia was diagnosed with clinical exam, ultrasound exam and x-ray of the hips. The exams were done in period of January 2012 to August 2014. RESULTS: Two groups of patients were formed. The first one consisted of premature infants, total number of 75 (34 girls and 41 boys), with developmental hip dysplasia that was diagnosed at the first exam at the Ultrasound unit of the Pediatric clinics and at the Intensive Neonatal Care Unit of the Pediatric Clinics in Sarajevo. Second (control) group consistsed of patients-on term infants who had diagnosed one of developmental hip dysplasia, total of 75 (43 girls and 32 boys) during first exam in the Ultrasound unit of the Pediatric clinics in Sarajevo. CONCLUSION: The frequency of premature birth is between 5 and 10% of all labors and demonstrates increasing trend. We suggest ultrasound examination of hips in each newborn, term or premature, at the age of 6 weeks after birth.